THE IMPLEMENTATION OF GENRE-BASED APPROACH IN TEACHING WRITING BY A UNIVERSITY TEACHER IN JOMBANG - Fanani, Achmad (JURNAL SMART, 2018)
This current research describes the application of GBA in teaching writing to university students. It was conducted by observing an English teacher in implementing GBA in his class. The result showed that he had fully implemented GBA which worked very well with the students in the beginner level. The roles of the teacher found were as an expert (BKOF, MOT), a resource person (BKOF), a director (BKOF), a facilitator (BKOF, JCOT), an observer (JCOT), feedback giver (JCOT, ICOT). The result implies that GBA is effective to improve the studentsâ writing skill and should be considered to implement in writing classes.Â